Public utility beta adjustment and biased costs of capital in public utility rate proceedings - Michelfelder, Richard A.; Theodossiou, Panayiotis (My University, 2013)
The Capital Asset Pricing Model (CAPM) is commonly used in public utility rate proceedings to estimate the cost of capital and allowed rate of return. The beta in the CAPM associates risk with estimated return. However, an empirical analysis suggests that the commonly used Blume CAPM beta adjustment is not appropriate for electric and electric and gas public utility betas, and may bias the cost of common equity capital in public utility rate proceedings.
Keywords: Capital Asset Pricing Model; CAPM